2023
DOI: 10.1002/vro2.58
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of small intestinal intussusception in 126 cattle in Switzerland

Abstract: Background Intussusception is a form of ileus of the intestines in which an oral intestinal segment slides into the adjacent aboral intestinal segment, causing obstruction of the bowel. Methods We analysed the medical records of 126 cattle with intussusception of the small intestine. Results Demeanour and appetite were abnormal in 123 cattle. Non‐specific signs of pain occurred in 26.2%, signs of visceral pain in 46.8% and signs of parietal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
3
13
0
1
Order By: Relevance
“…The present study found that period of birth had a significant effect on calf mortality. These findings were consistent with previous reports of various researchers (Braun et al, 2012;Hegazy et al, 2016;König et al, 2018;Upadhyay et al, 2017;Zhang et al, 2019). The lower mortality rates in calves born in later periods compared to former periods under the present study may be due to improved management practices and better environmental conditions during these periods.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The present study found that period of birth had a significant effect on calf mortality. These findings were consistent with previous reports of various researchers (Braun et al, 2012;Hegazy et al, 2016;König et al, 2018;Upadhyay et al, 2017;Zhang et al, 2019). The lower mortality rates in calves born in later periods compared to former periods under the present study may be due to improved management practices and better environmental conditions during these periods.…”
Section: Discussionsupporting
confidence: 94%
“…The higher mortality rate in male calves born in the rainy season may be due to the increased prevalence of infectious diseases and poor environmental conditions during this time (Braun et al, 2012). The study findings highlight the importance of implementing effective management strategies that take into consideration environmental factors to mitigate mortality rates in the dairy industry, particularly in calves up to 1 year of age.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Signs of pain were judged as mild, moderate or severe as described [ 20 ]. In addition, the cows were assigned to the colic, indolence or intoxication phase depending on the stage of illness [ 17 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In humans, ultrasound has been developed extensively during the past seventy years and it currently being implemented in general practice (Andersen et al 2019;Díaz-Gómez et al 2021;Nielsen et al 2021). In veterinary medicine, diagnostic ultrasound is used during the past two decades on a large scale as a safe, fast and non-invasive methodology for the early detection, diagnosis and prognosis of different animal diseases (Crilly 2022;Sary et al 2022;Braun et al 2023;Turner et al 2023). The technique is used also for guidance during treatment procedures and also for biopsy of tissue specimens for confirmatory diagnosis by histopathological examination (Shimizu et al 2021;Hawkins et al 2022;Scheemaeker et al 2023).…”
Section: Introductionmentioning
confidence: 99%